Powder property, microstructure, and creep behavior of a P/M Mo-Si-B based alloy. (15th January 2021) - Higashi, Masaya; Ozaki, Tomomichi
Abstract: This study was the first to apply powder metallurgy for the fabrication of a MoSiBTiC alloy. Spherical MoSiBTiC alloy powders were manufactured by ingot crushing, plasma spheroidization, and gas atomization, and the effects of the powder manufacturing methods on the powder characteristics, sintered microstructures, and creep behaviors were elucidated. The plasma-spheroidized (PS) powder exhibited the highest flowability due to the excellent particle circularity of 0.94; however, its oxygen content was much higher than that of the gas-atomized (GA) powder. The GA powder exhibited an extremely low oxygen content of 390 ppm; however, its flowability was lowered because of many irregular-shaped particles. The consolidation of these powders by hot isostatic pressing (HIP) was completed, and a fully dense sample without any defects could be obtained for all the powders regardless of the flowability. The cross-sectional microstructures of the powder particles were largely varied depending on the powder fabrication methods, which resulted in the formation of different HIP microstructures. The high-temperature creep behavior was strongly dependent on the HIP microstructure. The HIP sample fabricated from the crushed powder exhibited the highest creep resistance due to the coarse microstructure compared to other samples with equiaxed microstructures fabricated from PS and GA powders. Graphical abstract: Unlabelled Image Highlights: Plasma-spheroidized powder exhibited the excellent powder flowability equivalent to the commercial powders. Rapidly solidified microstructures of the plasma-spheroidized and gas-atomized particles were characterized. Fully dense MoSiBTiC alloy samples without any defects were obtained by powder hot isostatic pressing. The equiaxed grain microstructure could be achieved by applying the powder metallurgy route.